An overview of mixed methods research - revisited. - DOYLE, LOUISE; BYRNE, GOBNAIT; BRADY, ANNE-MARIE (My University, 2016)
Mixed methods has become increasingly popular in health related research allowing a broader and deeper understanding of complex human phenomena. This growth in popularity has increased the range of usage and complexity in design approaches producing greater need for understanding of logistical and practical application in this field. This paper aims to provide an overview of mixed methods research and orientate to the critical issues that arise for researchers. It provides an introduction to mixed methods design and the rationale and philosophical underpinnings for this methodological approach. It navigates the reader through some of real world or ‘hot topics’ within mixed methods including data analysis, integration and quality appraisal criteria.
PUBLISHED
Keywords: Mixed methods, qualitative research, quantitative research, integration, healthcare research.; Mixed Methods Research